Parenting Style and Emotional Well-Being Among Adolescents: The Role of Basic Psychological Needs Satisfaction and Frustration - Abidin, Fitri Ariyanti; Yudiana, Whisnu; Fadilah, Syipa Husni (Frontiers in Psychology, 2022)
The research examined the relationship between supportive parenting styles (warmth, structure, and autonomy support) and emotional well-being and whether they are mediated by basic psychological need satisfaction. It also explores thwarting parenting styles (rejection, chaos, and coercion) that may be associated with emotional ill-being, mediated by basic psychological needs frustration. This study involved 394 Indonesian adolescents aged 11-15 years old (49.5% boys, 50.5% girls) as the participants. We employed the structural equation model (SEM) analysis to evaluate the hypotheses. The research found that basic psychological needs satisfaction fully mediated the relationship between supportive parenting styles and emotional well-being; basic psychological needs frustration fully mediated the relationship between thwarting parenting styles and emotional ill-being (Chi-Square = 434.39; df= 220; p= .000; RMSEA= .05; CFI = .91; GFI =.91; SRMR= .05). Interestingly, the findings indicate that the thwarting parenting style positively influences basic psychological needs satisfaction. The research concludes that supportive parenting enhances the well-being of adolescents by satisfying their basic psychological needs. However, thwarting parental behaviors did not forestall the satisfaction of needs. The way Indonesian adolescents perceived the thwarting parenting style was discussed.